TECHNOLOGY FORESIGHT OF PATENT MANAGEMENT: AN OVERVIEW ON BIG DATA FOR REPOSITORY FIELDS - Tommy Hendrix (Jurnal Bisnis Manajemen, 2019)
The development of technology for entering the revolution industries 4.0 era nowadays becomes a hot issue in all industries. This condition is more interesting to discover in reducing budget expenditure, especially in the production process and obtaining raw materials. One of the tools that can be used is through technology foresight in patent management to see more information and predict the advanced technology which brings a competitive advantage in the digital era. Big data in fields of the repository is an urgent requirement, especially in collecting data from R D results. So, it will facilitate data retrieval within a specific time. This paper discusses how a user knows the development and predicts technology for market segmentation through a patent portfolio, licensing, status, competitor, innovation, and monitoring emerging market with a patent database registered on WIPO. The methodology used software Innography (Licensed). This paper aims to analyze patent database of big data for repository, related to the development of technology foresight products that have been produced, as well as to study the competitors’ movement. The result shows that there are 1262 registered patents with seventeen patents and six organizations acting as assignees from 2004 until 2018. This paper is beneficial to the industry and stakeholders needing the impact of the implementation of the latest technology and the appropriate level of competition in the commercialization of big data for the repository as a digital system for information technology.